Encountering God : a spiritual journey from Bozeman to Banaras - Eck, Diana L. (New Delhi : Penguin Book, 1995)
In the summer of 1965, as young Americans everywhere struggled to come to terms with the war in Vietnam and the crises of the civil rights movement, Diana Eck was a college student learning Hindi in preparation for her first visit to India. It was a trip that would change her life, bringing her into relationships with non-Christians such as the former freedom fighter Achyut Patwardhan and the philosopher Krishnamurti, whose insights challenged her to examine her own Christian faith from a radically new perspective. Now in the 1990s the challenge of responding to the problem of religious difference is virtually universal. Is only one religion true? Is there a way ahead in a world of interreligious strife? Today most Americans have encountered religions not their own: a neighbor practices Buddhist meditation, one's child has a Muslim classmate, or a friend extends an invitation to a Christmas Eve service or a Passover seder. In Encountering God, Eck reflects on the questions posed by her own ongoing encounter with Hindus, Buddhists, and Muslims. Her vivid story reminds us that interfaith dialogue'does not usually begin with philosophy or theory, but with experience and relationships.' Eck considers the spiritual questions that perplex each of us, Hindu or Christian, devout or not: Who is God? How are we to pray? What are we to believe in the face of inexplicable suffering and death? Eck insists as a Christian that her relations with people of other faiths have helped her to think about these questions and deepened her own faith. Above all, Encountering God instructs us in the urgent need for dialogue among the world's faiths as we enter the twenty-first century. Eck believes understanding between Christians and people of other faiths is not only possible but essential to our common future. As we confront our growing interdependence in a global community, she argues that we must all reach beyond mere'tolerance' of other religions toward a genuine pluralism based on respect for religious differences and openness to mutual transformation.
1. Bozeman to Banaras: Questions from the Passage to India -- 2. Frontiers of Encounter: The Meeting of East and West in America since the 1893 World's Parliament of Religions -- 3. The Names of God: The Meaning of God's Manyness -- 4. The Faces of God: Discovering the Incarnation in India -- 5. The Breath of God: The Fire and Freedom of the Spirit -- 6. Attention to God: The Practice of Prayer and Meditation -- 7.'Is our God Listening?': Exclusivism, Inclusivism, and Pluralism -- 8. The Imagined Community: Spiritual Interdependence and a Wider Sense of'We'.
Includes bibliographical references (pages [245]-251) and index.
Keywords: Eck, Diana L; Christianity and other religions